Species diversity and systematics of the Leptodactylus melanonotus group (Anura, Leptodactylidae): review of diagnostic traits and a new species from the Eastern Guiana Shield. Issue 1 (31st December 2022) - Carvalho, Thiago R.; Fouquet, Antoine; Lyra, Mariana L.; Giaretta, Ariovaldo A.; Costa-Campos, C. Eduardo; Rodrigues, Miguel T.; Haddad, Célio F. B.; Ron, Santiago R.
Abstract : The Leptodactylus melanonotus species group is an anuran clade widely distributed in the Neotropics. This clade harbours many species that are difficult to identify because of incomplete taxonomic knowledge, ambiguous species boundaries and distribution. Here we expand the understanding of species diversity of this Leptodactylus clade by analysing mtDNA sequences for over 600 individuals, delimiting Operational Taxonomic Units (OTUs), and updating species identifications and distributions by linking sequences to morphotypes and calls. Also, we review the morphological and acoustic traits traditionally used as diagnostic characters of species within this group. The DNA-based species delimitation analyses yielded 57 OTUs. Given that only 19 taxa are currently recognized as valid species, our results suggest the existence of many unnamed species within the L. melanonotus group. After reassessing morphological traits in the group, we concluded that the combined use of dorsolateral fold, upper lip stripe, and belly colouration is sufficiently informative for species identification in most cases, especially when associated with data on geographic distribution and habitat use. Regarding advertisement calls, the patterns of amplitude and frequency modulation, calling rate, and dominant frequency were also informative for species discrimination. Furthermore, we designate a neotype for L. wagneri, for which we also describe the advertisement call, and make comparisons with congeners of the L. melanonotus group, especially with the partially sympatric L. leptodactyloides . Lastly, we name and describe a new species endemic to the Eastern Guiana Shield. Patterns of distribution and habitat use in the L. melanonotus group revealed that sympatric occurrences are more commonly found among distantly related species, whereas allopatric occurrences correspond to closely related ones. Speciation between closely related species of the group seems to be related to ecological divergence (open vs. forest habitats) in parallel with clear morphological and acoustic differentiation. http://www.zoobank.org/urn:lsid:zoobank.org:pub:867A8EA9-A8F2-4FA4-8746-A0D9BB2E4286